Drought, bank lending, and agricultural financial resilience - Brei, Michael; Kowalewski, Oskar; Śpiewanowski, Piotr; Strobl, Eric (Journal of Corporate Finance, 2026)
Drought can tighten agricultural credit conditions precisely when adaptation investments and access to working capital are most valuable. Using bank balance-sheet data merged with county-level U.S. Drought Monitor data for 2000–2020, we show that local credit markets exposed to drought experience significant declines in agricultural lending, with effects concentrated in severe episodes. These declines are strongest in markets served by geographically concentrated banks, especially single-county institutions, and weaker where lenders are more geographically diversified. In addition, we show that counties with greater irrigation intensity experience smaller lending declines during extreme droughts, while drought-related contractions are concentrated in counties with lower baseline crop resistance. Lending responses are also larger in counties with prior drought experience, consistent with persistent climate risk shaping local credit conditions. Our evidence highlights how climate risk, local adaptation, and bank structure jointly determine the availability of agricultural credit during drought episodes.